Healing of a soft tissue wound of the neck and jaw osteoradionecrosis using platelet gel. (July 2016) - Piccin, Andrea; Di Pierro, Angela Maria; Tagnin, Mario; Russo, Carla; Fustos, Roland; Corvetta, Daisy; Primerano, Marco; Magri, Elena; Conci, Viviana; Gentilini, Ivo; Burchia, Evelin; Negri, Giovanni; et al.
Aim: Bone osteoradionecrosis is a serious complication of radiation treatment. Current treatment approaches are not curative and treatment response is often poor leading to high social and healthcare costs.Case report: We report on the first case of osteoradionecrosis with successful restitutio ab integro by repeated administration of platelet gel (PLT-gel) and surgery in a critically ill patient. The administration of PLT-gel during a severe septic episode helped regeneration of bone and soft tissues, shortening the hospital stay of the patient. It was also noted that following applications of PLT-gel, both the use of morphine and the numbers of infective episodes were reduced.Conclusion: Additional studies are needed to confirm the promising effect of PLT-gel for the treatment of osteoradionecrosis.